Intracorporeal Anastomoses in Minimally Invasive Right Colectomies Are Associated With Fewer Incisional Hernias and Shorter Length of Stay. Issue 5 (May 2020) - Widmar, Maria; Aggarwal, Piyush; Keskin, Metin; Strombom, Paul D.; Patil, Sujata; Smith, J. Joshua; Nash, Garrett M.; Garcia-Aguilar, Julio
Abstract : BACKGROUND: Intracorporeal anastomosis is associated with several short-term benefits. However, it is a technically challenging procedure with potential risk OBJECTIVE: The purpose of this study was to investigate differences in short-term complications and long-term incisional hernia rates after robotic right colectomy with intracorporeal versus extracorporeal anastomoses and standardized extraction sites. DESIGN: This was a historical cohort study. SETTINGS: The study was conducted at a single institution. PATIENTS: All of the patients undergoing robotic right colectomy with intracorporeal anastomosis and a Pfannenstiel extraction site or extracorporeal anastomosis with a vertical midline extraction site from 2013 to 2017 were eligible. Exclusion criteria were conversion to laparotomy for tumor-related reasons or lack of follow-up. INTERVENTION: Intracorporeal or extracorporeal anastomosis was performed, based on availability of the robotic stapler and appropriate bedside assistance. MAIN OUTCOME MEASURES: The primary outcome was incisional hernia, diagnosed either clinically or on postoperative imaging, and analyzed using time-to-event analysis. A Cox proportional hazards model was used for multivariable analysis. Secondary outcomes were analyzed using parametric and nonparametric tests. Statistical significance was set at p < 0.05. RESULTS: Of 164 patients who met all inclusion criteria, 67 had intracorporeal and 97 had extracorporeal anastomoses. Median follow-up time was similar in both groups (14 vs 15 mo; p = 0.73). The 1-year estimated incisional hernia rate was 12% for extracorporeal and 2% for intracorporeal anastomoses (p = 0.007); this difference was confirmed by multivariable modeling. The severity of postoperative complications was similar between the groups, but there was an increase in incisional infections and a shorter length of stay (1 day) for intracorporeal cases. LIMITATIONS: The study was limited by its retrospective, single-surgeon nature. CONCLUSIONS: Right colectomy with intracorporeal anastomosis and a Pfannenstiel extraction site may reduce the rate of incisional hernias compared with extracorporeal anastomosis with a vertical midline extraction site. The intracorporeal approach was also associated with a decreased length of stay but an increase in incisional surgical site infections. These findings have implications for healthcare use and patient-centered outcomes. See Video Abstract at http://links.lww.com/DCR/B147 . ANASTOMOSIS INTRACORPÓREAS EN COLECTOMÍAS DERECHAS MÍNIMAMENTE INVASIVAS SE ASOCIAN CON MENOS HERNIAS INCISIONALES Y UNA ESTADÍA HOSPITALARIA MÁS BREVE: ANTECEDENTES: nastomosis intracorpórea se asocia con varios beneficios a corto plazo. Sin embargo, es un procedimiento técnicamente desafiante con riesgos potenciales. OBJETIVO: nvestigar las diferencias en las complicaciones a corto plazo y las tasas de hernia incisional a largo plazo después de la colectomía robótica derecha con anastomosis intracorpórea versus extracorpórea y sitios de extracción estandarizados. DISEÑO: Estudio de cohorte histórico. ENTORNO CLÍNICO: cirujano individual, institución única. PACIENTES: Todos los pacientes sometidos a colectomía robótica derecha con anastomosis intracorpórea y un sitio de extracción de Pfannenstiel o anastomosis extracorpórea con un sitio de extracción vertical de la línea media de 2013-2017 fueron elegibles. Los criterios de exclusión fueron la conversión a laparotomía por razones relacionadas con el tumor o la falta de seguimiento. INTERVENCIÓN: nastomosis intracorpórea o extracorpórea, según la disponibilidad de grapadora robótica y la asistencia adecuada quirúrgica. PRINCIPALES MEDIDAS DE VALORACIÓN: El resultado primario fue la hernia incisional, diagnosticada clínicamente o en imágenes postoperatorias, y analizada mediante análisis de tiempo hasta el evento. Se usó un modelo de riesgos proporcionales de Cox para el análisis multivariable. Los resultados secundarios se analizaron mediante pruebas paramétricas y no paramétricas. La significación estadística se estableció en p < 0, 05. RESULTADOS: De 164 pacientes que cumplieron con todos los criterios de inclusión, 67 tenían anastomosis intracorpóreas y 97 tenían anastomosis extracorpóreas. La mediana del tiempo de seguimiento fue similar en ambos grupos (14 versus 15 meses, p = 0, 73). La tasa de hernia incisional estimada para un año fue del 12% para las anastomosis extracorpóreas y del 2% para las anastomosis intracorpóreas ( p = 0, 007); esta diferencia fue confirmada por el modelado multivariable. La gravedad de las complicaciones postoperatorias fue similar entre los grupos, pero hubo un aumento de las infecciones incisionales y una estancia más corta (un día) para los casos intracorpóreos. LIMITACIONES: Retrospectiva, cirujano único. CONCLUSIONES: a colectomía derecha con anastomosis intracorpórea y un sitio de extracción de Pfannenstiel puede reducir la tasa de hernias incisionales en comparación con la anastomosis extracorpórea con un sitio de extracción vertical en la línea media. El enfoque intracorpóreo también se asoció con una disminución de la duración de la estadía, pero con un aumento de las infecciones del sitio quirúrgico incisional. Estos hallazgos tienen implicaciones para la utilización de recursos médicos y beneficios para pacientes. Consulte Video Resumen en http://links.lww.com/DCR/B147 . (Traducción—Dr. Adrian Ortega).